2005
DOI: 10.3748/wjg.v11.i8.1091
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience from a combination of systemic and regional chemotherapy in the treatment of patients with nonresectable cholangiocellular carcinoma in the liver

Abstract: The present results indicate that a combination of systemic gemcitabine therapy and repeated regional chemoembolizations is well tolerated and may enhance the effect of palliation in a selected group of patients with intrahepatic nonresectable CCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…[39][40][41][42] Previous studies showed that TACE is an effective alternative treatment and recommended therapy for unresectable CCC with positive effects on the tumor-associated symptoms. 23,[44][45][46] In the current study, 115 patients with unresectable CCC were repeatedly treated with TACE. We achieved median and mean survival time of 13 and 20.8 months from the start of TACE, and the survival rate was 52% at 1 year, 29% at 2 years and 10% at 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42] Previous studies showed that TACE is an effective alternative treatment and recommended therapy for unresectable CCC with positive effects on the tumor-associated symptoms. 23,[44][45][46] In the current study, 115 patients with unresectable CCC were repeatedly treated with TACE. We achieved median and mean survival time of 13 and 20.8 months from the start of TACE, and the survival rate was 52% at 1 year, 29% at 2 years and 10% at 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Eight patients in the study of Kirchhoff et al 44 received TACE using Cisplatin, doxorubicin and degradable starch microspheres with systemic infusion of Gemcitabine chemotherapy. In this study the median survival time for the whole group was 12 months, and the median time to tumor progression was 7 months.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Although the drug concentration diminished with increased distance away from the implanted site, but 10 days after implantation, the drug concentration at 5 cm away from the implanted site was still higher than the lowest tumour-inhibiting concentration (0.05 μg/g) (Wang et al, 2012). The results also showed that there was a higher drug concentration in the portal vein 10 days after implantation (the lowest tumour-inhibiting concentration is 0.1 μg/g in the blood) (Kirchhoff et al, 2005), suggesting that it is of great importance for the prevention and treatment of liver metastasis. Besides, there was no visible necrosis at the local implanted tissue.…”
Section: Discussionmentioning
confidence: 62%
“…Median time from the first percutaneous intervention to the successful implantation of metal stent was 44 days, and the average number of percutaneous sessions totalled 5.2 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). This depended on the favorable effect of percutaneous drainage (for at least 2 weeks, with substantial improvement of laboratory tests), of the technique and the necessary time for histological confirmation of malignant stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…8 The combination of systemic chemotherapy (gemcitabine) and regional chemoembolizations may enhance the effect of palliation in a selected group of patients with a 21.1-23 months (1, 2, and 3-year survival rates 51.3%, 27.5%, and 27.5%, respectively) reported median of overall survival. [9][10][11] The potential benefit of regional chemotherapy with port system implanted percutaneously in intrahepatic cholangiocarcinoma (CC) was also reported by Tanaka et al 12 with a 26-month mean overall survival. All in all, intra-arterial therapies (chemoembolizations and chemoperfusions) offer a potential benefit and prolonged survival for patients with unresectable cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 89%